Complications, Reasons for Reoperation, and 5-Year Prosthesis Survival Compared between the Cemented and Cementless Oxford Unicompartmental Knee Arthroplasty in Thai Patients - Paugchawee J. (2023)
Background: Oxford unicompartmental knee arthroplasty (OUKA) yields favorable outcomes in patients with medial compartmental knee osteoarthritis. However, it remains unknown whether cemented or cementless OUKA fixation delivers better outcomes in Asian population. Objective: To investigate the complications, reasons for reoperation, and 5-year prosthesis survival compared between cemented and cementless OUKA in Thai patients. Materials and Methods: Four hundred sixty-six cemented and 36 cementless OUKA performed between 2011 and 2015 with a minimum follow-up of five years were included. With reoperation for any reason as the endpoint, Kaplan-Meier analysis was performed to compare 5-year implant survival between groups. Complications, reasons for reoperation, and 90-day morbidity and mortality were compared between groups. Cox proportional hazards model was used to identify independent predictors of implant survival. Results: There was no significant difference in 5-year implant survival between the cemented and the cementless groups at 96.4% versus 94.4% (p=0.375). The mean implant survival time was 113.0±0.8 and 70.8±1.9 months in the cemented and the cementless groups, respectively (p=0.383). The most common reason for reoperation was bearing dislocation, and only one patient had 90-day morbidity. There was no significant difference between groups for complications or reasons for reoperation. No independent predictors of implant survival were identified in multivariate analysis. Conclusion: OUKA was shown to be a safe and durable reconstructive procedure in Thai patients with medial compartmental knee osteoarthritis. There was no significant difference in implant survival between the cemented and the cementless groups during the 5-year follow-up, and no independent predictors of implant survival were identified.